Persistent goiter with congenital hypothyroidism due to mutation in DUOXA2 gene - Jung, So Yoon; Lee, Jeongho; Lee, Dong Hwan (Annals of pediatric endocrinology & metabolism, 2020)
Thyroid hormones are crucial for development of the central nervous system. Congenital hypothyroidism (CH) is the most common preventable disease resulting in mental retardation. A neonatal screening test (NST) can detect a mild form of CH that can be treated at an early age. Generally after 3 years of age, when most of the brain has matured, clinicians consider reevaluation of thyroid function for CH patients that have been identified with a normal thyroid gland at a normal position. This report presents three CH patients that developed normally, with persistent goiter despite thyroid hormone supplements. The patients' initial thyroid-stimulating hormone (TSH) level after NST was 47, 157, and 57 mIU/L, respectively. Levothyroxine administration began at 1 or 2 months of age and was terminated after reevaluation at the age of 3, 15, and 5 years, respectively. However, 1 or 2 years later, they all resumed their medication due to increased TSH level coupled with newly developed or enlarged goiter. They all showed dual oxidase maturation factor 2 (DUOXA2) gene mutation: a homozygous mutation with DUOXA2 (c.413dupA; p.Tyr138*) in case 1, a presumed compound heterozygotic mutation with DUOXA2 (p.Tyr138*/p.Tyr246*) in case 2, and heterozygous mutations with DUOXA2 (c.738C>G; p.Tyr246*) and TPO (c.2268dupT; p.Glu757*) in case 3. When goiter persists or is newly developed despite a maintained euthyroid status, for those with transient CH history, follow-up to assess the thyroid function is recommended for at least 1 or 2 years, and genetic testing would be helpful. This study presents the first clinical cases of DUOXA2 mutation in Korea.